(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the results of emergency treatment of supraventricular tachycardia in children according to the APLS 2021 protocol at the Emergency Department - National Children’s Hospital. Subjects and research methods: Children who were diagnosed with supraventricular tachyarrhythmias when admitted to the Emergency - Anti-toxicity Department of the National Children’s Hospital. Results: Children over one year old accounted for the majority (76%). There are 46 cases of successful cessation, accounting for 92%. Treating supraventricular tachycardia is mainly used with drugs (accounting for 90), in which adenosine is primarily used (96%). There were 76.6% cases of successful cessation with adenosine and the highest rate of successful termination of the second dose, accounting for 57.7%. The rate of successful cessation in the group of children under one year old and over one year old did not have a statistically significant difference (p>0.05). The rate of acute heart failure decreased compared to before cessation with a difference with statistical significance p < 0.05. Conclusion: Adenosine is an effective, safe, first-choice drug in managing supraventricular tachycardia in children.